DFT and TD-DFT Study of Only First Diaminomalenonitrile Based Molecular Receptor for Fluoride Anion: Correlation of Calculated and Experimental Results - Kaloo, M. A.; Bashir, H.; Rather, M. A.; Majid, S. A.; Bhat, B. A. (Journal of Scientific Research, 2021)
In this work, the sensing mechanism of a novel anion receptor, 2-amino-((E)-(4-cyanobenzalidine) amino) maleonitrile reported by Sankar et al. (Analyst 138:4760-4763, 2013) was investigated theoretically with the help of density functional theory (DFT) and time-dependent density functional theory (TD-DFT). From the frontier molecular orbital analysis, it is reasonable to support the proposed charge transfer (ICT) enhancement in the receptor molecule in the presence of F−. A significant reduction in the energy gap (ΔE) from 4.014 eV to 2.342eV between highest occupied and lowest unoccupied energy levels was revealed, leading to the strong redshift of its absorption characteristics. Moreover, 1H NMR was also calculated to further understand the mechanistic insights by using the gauge independent atomic orbital (GIAO) method with B3LYP methods and the 6-311++G (d,p) basis set. The spectra were simulated, and the chemical shifts linked to TMS were compared with experimental. Besides, Intrinsic Reaction Coordinates (IRC) were also calculated to understand the sensing mechanism.